Smoking in Patients With Chronic Cardiovascular Disease During COVID-19 Lockdown - Chagué, Frédéric; Boulin, Mathieu; Eicher, Jean-Christophe; Bichat, Florence; Saint-Jalmes, Maïlis; Cransac, Amélie; Soudry, Agnès; Danchin, Nicolas; Laurent, Gabriel; Cottin, Yves; Zeller, Marianne (Frontiers in Cardiovascular Medicine, 2022)
Objectives This cross-sectional study aims to investigate health-related behaviours including tobacco consumption among patients with cardiovascular (CV) diseases, during the first COVID-19-related lockdown. Methods After 5 weeks of COVID-19 lockdown, 220 patients with chronic coronary syndromes (CCS] and 124 with congestive heart failure (CHF) answered a phone questionnaire. Results Among these 344 patients, 43 (12.5%) were current smokers, and none had quit during the lockdown. When compared with non-smokers, smokers were 15 years younger, more often diabetic, more likely to live in an urban than a rural lockdown location, and more often in the CCS cohort (p=0.011). Smokers described greater psychological impairment, but their rates of decrease in physical activity and of increase in screen time were similar to non-smokers. More than one third (13/43) increased their tobacco consumption, which was mainly related to stress or boredom, but not driven by media messages on a protective effect of nicotine. Conclusions Given the major impact of persistent smoking in patients with cardiovascular disease, these findings suggest that lockdown periods may result in poorer prognoses, highlighting the need for targeted prevention strategies.